Proteus ISIS simulation for power factor calculation using zero crossing detector - Jumrianto Jumrianto; Royan Royan (National Research and Innovation Agency, 2021)
One of the important parameters for electrical systems is the power factor (cos phi), which is the ratio of the real power (watt) to the apparent power (volt ampere). The best cos phi value is between 0.85 to 1. A resistive load causes the voltage and current in equal phase angle, while the inductive load causes the current to lag behind the voltage. On the other hand, the capacitive load causes the current to precede the voltage (leading). A simulation to determine the power factor of an electrical network can be done with Proteus ISIS software by creating a phase detection circuit. Automatic control can be done by a microcontroller. This simulation circuit can be used as power factor correction, a trigger angle on SCR trigger for DC motor speed control, for rocket launch angle adjuster, to measure the angle of inclination, and other uses relating to angle adjustments.